Zebrafish and Medaka: Two Teleost Models of T-Cell and Thymic Development - Bajoghli, Baubak (Int J Mol Sci, 2019)
Over the past two decades, studies have demonstrated that several features of T-cell and thymic development are conserved from teleosts to mammals. In particular, works using zebrafish (Danio rerio) and medaka (Oryzias latipes) have shed light on the cellular and molecular mechanisms underlying these biological processes. In particular, the ease of noninvasive in vivo imaging of these species enables direct visualization of all events associated with these processes, which are, in mice, technically very demanding. In this review, we focus on defining the similarities and differences between zebrafish and medaka in T-cell development and thymus organogenesis; and highlight their advantages as two complementary model systems for T-cell immunobiology and modeling of human diseases.